"How Often? How Much? Where From?" Knowledge, Attitudes, and Practices of Mothers and Health Workers to Iron Supplementation Program for Children Under Five in Rural Tamil Nadu, South India. (July 2014) - Kwon, Hye Jin; Ramasamy, Rajkumar; Morgan, Alison
Iron deficiency anemia (IDA) affects 70% of under-5 children in India. The primary prevention strategy is regular iron supplementation. Little is known about what helps families adhere to daily iron supplementation. Our study explored the knowledge, attitudes, and practices of mothers and village health workers (VHWs) involved in a community health program in one hill district of Tamil Nadu. We conducted 30 semistructured interviews and 3 group discussions involving mothers, VHWs, and community stakeholders. Knowledge of IDA was widespread, yet no children were receiving the iron supplementation as recommended. The main determinants to adherence included the perception of its need, the ease of access, and the activity of VHWs. Preventive care requiring daily supplements is challenging. Our study suggests that increasing community awareness of mild anemia, simplifying dosage instructions, and further strengthening the supportive environment for VHWs would help in reducing the prevalence of IDA.